A case report of ectopia cordis and omphalocele - Taksande, Amar M (Medknow Publications & Media Pvt Ltd, 2013)
A rare congenital defect in fusion of the anterior chest wall resulting in an extrathoracic location of the heart. Cantrell's pentalogy is a congenital anomaly resulting from embryologic development defect and consists of the following: A deficiency of the anterior diaphragm, a midline supraumbilical abdominal wall defect, a defect in the diaphragmatic pericardium, congenital intracardiac abnormalities, and a defect of the lower sternum. Here we report a rare case of ectopic cordis with omphalocele.